Cycling Rate‐Induced Spatially‐Resolved Heterogeneities in Commercial Cylindrical Li‐Ion Batteries. Issue 9 (16th August 2021) - Vamvakeros, Antonis; Matras, Dorota; Ashton, Thomas E.; Coelho, Alan A.; Dong, Hongyang; Bauer, Dustin; Odarchenko, Yaroslav; Price, Stephen W. T.; Butler, Keith T.; Gutowski, Olof; Dippel, Ann‐Christin; Zimmerman, Martin von; et al.
Abstract: Synchrotron high‐energy X‐ray diffraction computed tomography has been employed to investigate, for the first time, commercial cylindrical Li‐ion batteries electrochemically cycled over the two cycling rates of C/2 and C/20. This technique yields maps of the crystalline components and chemical species as a cross‐section of the cell with high spatiotemporal resolution (550 × 550 images with 20 × 20 × 3 µ m 3 voxel size in ca. 1 h). The recently developed Direct Least‐Squares Reconstruction algorithm is used to overcome the well‐known parallax problem and led to accurate lattice parameter maps for the device cathode. Chemical heterogeneities are revealed at both electrodes and are attributed to uneven Li and current distributions in the cells. It is shown that this technique has the potential to become an invaluable diagnostic tool for real‐world commercial batteries and for their characterization under operating conditions, leading to unique insights into "real" battery degradation mechanisms as they occur. Abstract : X‐ray diffraction computed tomography is employed to study commercial cylindrical Li‐ion batteries electrochemically cycled at C/2 and C/20 rates. The chemical maps reveal heterogeneities at both electrodes which are related to uneven Li and current distribution in the cells. The current work demonstrates the unique spatially‐resolved physico‐chemical information obtained with this technique from industrially‐relevant energy storage devices.